EFL Teachers’ Readiness In Using ICT: Knowledge, Skills, and Attitudes - Norasiah Norasiah; Selvia Irawan; Annisa Amriani; Ade Liany Putri (Jurnal Edusci, 2025)
Aims. This research investigates English teachers’ preparedness to integrate Information and Communication Technology (ICT) into their teaching practices in the post-pandemic context. The study specifically focuses on three objectives: (1) to assess the level of readiness demonstrated by English teachers in adopting ICT after the pandemic; (2) to explore the ways in which teachers utilize ICT tools within classroom instruction; and (3) to identify the primary barriers and difficulties teachers encounter when implementing ICT in the post-pandemic period. Methods. Employing a mixed-methods approach, this study integrates both quantitative and qualitative data to provide a comprehensive understanding of the topic. The quantitative component examines variable relationships based on established theoretical frameworks, while qualitative inquiry supports deeper contextual interpretation. Participants included 48 English teachers from public junior high schools in Yogyakarta City, with four teachers selected for in-depth interviews. The questionnaire was adapted from validated instruments developed by Singh and Chan (2014), Al-Furaydi (2013), Davis (1989), and Zara-ee (2011). Descriptive statistical analysis was used for quantitative data, and qualitative data were analyzed through the interactive model proposed by Miles et al. (2014). Results. Findings reveal that 74% of the participants exhibited a high level of ICT readiness, whereas 26% demonstrated limited preparedness. Conclusion. The interviews highlighted several obstacles hindering ICT integration, including unstable internet connectivity, financial limitations, insufficient ICT-related training, and inadequate school infrastructure. Implementation. The most prominent challenge identified in this research was the shortage of professional development opportunities or ICT training for teachers.